2018
DOI: 10.5005/jp-journals-10024-2206
|View full text |Cite
|
Sign up to set email alerts
|

Study Model-based Evaluation of Built-in Tip, Torque, and In–out Characteristics of a Third-generation Preadjusted Edgewise Appliance

Abstract: Aim:The aim of the study was to evaluate the clinical effectiveness of MBT™ preadjusted edgewise appliance (PEA) in terms of achieving the optimal expression of its built-in characteristics of tip, torque, and in-out. Materials and methods:Pretreatment and posttreatment study models of 20 subjects who received full fixed appliance treatment involving four first premolar extractions using the MBT™ appliance were measured for tip, torque, and in-out using the method described by Andrews. Treatment changes were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…2 Using 0.022" slots MBT bracket system which is a third-generation preadjusted edgewise appliance that introduces a range of improvements and specification changes to overcome the clinical shortcomings of earlier preadjusted edgewise bracket systems. 12 Present study showed that MBT appliance is effective in ensuring a successful treatment result, though individual adjustments may be necessary for optimal tooth positioning at the end of the treatment, as with any other preadjusted appliance. 12 Using 0.022" slots to perform more freedom of movement of initial aligning arch wires in the relatively larger slot is practiced; likewisenewer orthodontic alloys can be used in 0.022" slots with minimum patient discomfort and optimum clearance for sliding is obtained.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…2 Using 0.022" slots MBT bracket system which is a third-generation preadjusted edgewise appliance that introduces a range of improvements and specification changes to overcome the clinical shortcomings of earlier preadjusted edgewise bracket systems. 12 Present study showed that MBT appliance is effective in ensuring a successful treatment result, though individual adjustments may be necessary for optimal tooth positioning at the end of the treatment, as with any other preadjusted appliance. 12 Using 0.022" slots to perform more freedom of movement of initial aligning arch wires in the relatively larger slot is practiced; likewisenewer orthodontic alloys can be used in 0.022" slots with minimum patient discomfort and optimum clearance for sliding is obtained.…”
Section: Discussionmentioning
confidence: 70%
“…12 Present study showed that MBT appliance is effective in ensuring a successful treatment result, though individual adjustments may be necessary for optimal tooth positioning at the end of the treatment, as with any other preadjusted appliance. 12 Using 0.022" slots to perform more freedom of movement of initial aligning arch wires in the relatively larger slot is practiced; likewisenewer orthodontic alloys can be used in 0.022" slots with minimum patient discomfort and optimum clearance for sliding is obtained. 13,14 Leveling and aligning begins with NiTi round archwire; NiTi was used at the beginning because the wire bypasses 13 and 23.…”
Section: Discussionmentioning
confidence: 70%